Design and development of a data acquisition system for industrial or residential use - Chua, Su Ya (Nanyang Technological University, 2021)
Over the years many parts of the world have observed an increasing demand for electricity used in residential and industrial buildings. Mainly due to the fact that there is an increasing trend of rapid urbanization, economic growth, and population growth in the world. Thus, this project aims to develop a data acquisition system for both residential and industrial to monitor the load consumption and therefore reduce the total end-user electrical consumptions using non-intrusive load monitoring technic. Non-intrusive load monitoring (NILM) is a technic where the different loads of the appliances are monitored independently at a single point of the circuit by using only one sensor. NILM consists of both hardware and software integration. For the hardware, electrical data will be captured by Yokogawa CW240 Power meter and the data will then be transmitted over to the personal computer via RS-232 Bluetooth connection. For the software, both Excel Visual Basic for Applications (VBA) and LABVIEW will be used to design the disaggregation algorithm for steady-state analysis and separate the loads into individual components. Lastly, a graphic user interface (GUI) will also be developed to display all the required information to enhance efficiency and enable ease of use.